Нанотехнологічний оптичний сенсор для визначення органічних речовин у водних об’єктах - Логунов, В. С.; Сушко, О. А. (ХНУРЕ, 2023)
In abstract a problem is considered concerning the definition in water objects of organic substances such as polycyclic aromatic hydrocarbons (PAH). Optical sensor for organic substances detection is developed. It represents portable device which is based on semiconductor quantum dots which are the detector elements of optical sensor. The principle of optical sensor operation is based on electrochemical and electrochemiluminescence methods using modern nanomaterials and nanotechnologies. It can be used in medicine and ecology for investigation and monitoring of water object for PAH content detection.